Influence Factors for Decision-Making Performance of Suicide Attempters and Suicide Ideators: The Roles of Somatic Markers and Explicit Knowledge - Wang, Lingling; Li, Jingmin; Liu, Hailing; Wang, Zhongpeng; Yang, Li; An, Li (Frontiers in Psychology, 2021)
Impaired decision-making has been observed in suicide attempters during the Iowa Gambling Task (IGT). Decision-making performance is influenced by the somatic markers as well as explicit knowledge, but it is still unclear of the influencing role on decision-making performance in suicide individuals. We aimed to investigate whether there is decision-making deficit in suicide attempters and suicide ideators, as well as the distinct roles of somatic markers and explicit knowledge wherein. Thirteen suicide attempters, twenty-three suicide ideators and nineteen healthy controls performed the IGT. Both somatic markers (by the skin conductance responses, SCRs) and explicit knowledge (by the questionnaire) were recorded. No significant differences were found among three groups on IGT performance, explicit knowledge and anticipatory SCRs. IGT Performance of suicide attempters was positively correlated with explicit knowledge index while behavior performance was positively associated with the SCRs in healthy controls. These results indicate the suicide attempters applied a distinct strategy from healthy controls to perform normally in the IGT.